Efficacy of screening and treatment of latent tuberculosis infection. Issue 1 (2nd January 2017) - Varughese, Marie; Long, Richard; Li, Michael Y.
ABSTRACT: Sixty-three percent of the total active tuberculosis cases in Canada were diagnosed among foreign-born individuals, representing 20% of the total population. The majority of these cases occur from the reactivation of tuberculosis infections acquired prior to immigration. A preventive policy consisting of screening and treating new immigrants for latent tuberculosis infection is evaluated on its efficacy for reducing the total number of tuberculosis cases, using tuberculosis incidence data between 1986 and 1995 from the Canadian tuberculosis reporting system. The most effective intervention is to screen for and treat latent tuberculosis infection among arriving immigrants from countries of birth with a tuberculosis incidence rate greater than 15 cases per 100, 000.